Feasibility of groundwater abstraction and treatment for urban water supply - Blignault, Samantha Paige (University of Cape Town, 2020)
Water is one of Earth's most valuable resources and one of Earth's most threatened resources. Continuously increasing population growth coupled with changing climate has resulted in the depletion of water sources. As a result, investigations into alternative water sources are being conducted worldwide. One such alternative water source is groundwater abstraction. Groundwater abstraction involves the abstraction of water from an underground source. The volume of water that can be sustainably abstracted is governed by legislation. Groundwater typically requires treatment before it can be distributed to the general population for use, and thus the implementation of large-scale groundwater abstraction projects involves large capital outlays, as well as monthly operational outlays. The feasibility into the implementation of large-scale groundwater abstraction projects is therefore of interest to stakeholders involved in the water supply industry. The lifecycle of a recently implemented large-scale groundwater abstraction project was analysed in order to determine its feasibility. The project was implemented by Drakenstein Municipality in the Western Cape in 2017. The project involved identifying groundwater abstraction points that could provide sustainable volumes of water. The water quality of each groundwater abstraction point was then investigated for any outlying parameters according to SANS 241-1:2015 guidelines for potable water. Groundwater abstraction water treatment plants were then designed in order to treat the combined sustainable flow rates of water at their specific water qualities. The treated water from each groundwater abstraction water treatment plant was then analysed in order to confirm compliance with the SANS 241- 1:2015 guidelines, before the booster pumps were commissioned and commenced with their continuous supply of potable water into the network. The capital expenditure associated with each of the groundwater abstraction water treatment plants was obtained from the Engineer, Aurecon. In addition, the estimated monthly operational expenditure was computed. These expenditures were used to determine the feasibility of the large-scale groundwater abstraction project by computing the payback period and comparing this period to the design life of each of the groundwater abstraction water treatment plants. In addition, the monthly savings applicable to the municipality as a result of the project's implementation was computed. Finally, the feasibility into varying flow rates of groundwater abstraction water treatment plants, and varying water quality of groundwater abstraction points was investigated. Two sites were identified within the municipal area, each with four groundwater abstraction points capable of delivering a combined 5.18 ML/day and 1.62 ML/day. These sites were identified as Boy Louw Sportsgrounds and Parys Sportsgrounds respectively. Although the sites were only 2.60 kilometres apart, the water quality of the combined flow rates indicated that the groundwater abstraction points were accessing two different water sources. The combined sustainable flow rate at Boy Louw Sportsgrounds required turbidity, iron and manganese removal, as well as disinfection. The combined sustainable flow rate at Parys Sportsgrounds required turbidity removal and disinfection. Groundwater abstraction water treatment plants were then designed to treat the water at Boy Louw Sportsgrounds and Parys Sportsgrounds. Boy Louw Sportsgrounds involved the distribution of equipment across seven shipping containers, whilst Parys Sportsgrounds involved the distribution of equipment across three shipping containers. It was found that the groundwater abstraction project was feasible with a payback period of three years. This payback period fell well within the 10-year design life of each groundwater abstraction water treatment plant. In addition, it was found that the municipality would be subject to a 72% monthly saving in water costs as a result of utilising the groundwater abstraction water treatment plants, as opposed to purchasing water in bulk from the City of Cape Town. It was found that the payback periods of Boy Louw Sportsgrounds and Parys Sportsgrounds were two and five years respectively. Although Boy Louw Sportsgrounds delivered almost three times the potable water flow rate than that of Parys Sportsgrounds, its payback period was three years sooner. In addition, it was found that the municipal savings as a result of Boy Louw Sportsgrounds was 8% more than that of Parys Sportsgrounds. It was therefore concluded that the larger the flow rate of water to be treated, the more financially feasible the project. In addition, it was determined that the more water quality parameters lying above the upper limits of SANS 241-1:2015 guidelines for potable water, the more treatment processes would need to be implemented resulting in additional capital and operational expenditure. It was therefore concluded that the more water quality parameters requiring treatment, the less financially feasible the project. Finally, it was determined that the feasibility of the large-scale groundwater abstraction project is limited by the rate at which the municipality purchases water in bulk from the City of Cape Town. As long as the bulk water purchase tariff remains above R 2.85/m³, the project will remain feasible. Should the bulk water purchase tariff fall below this value, the project no longer remains feasible as the payback period of the project exceeds the design life of the groundwater abstraction water treatment plants.